Evaluation of bioactive glass scaffolds incorporating SrO or ZnO for bone repair: In vitro bioactivity and antibacterial activity. (August 2021) - Zhao, Rui; Shi, Lifen; Gu, Lin; Qin, Xusheng; Song, Zaizhi; Fan, Xiaoyun; Zhao, Ping; Li, Changqing; Zheng, Hailun; Li, Zhijun; Wang, Qizhi
A series of bioactive glass scaffolds doped with SrO or ZnO (0, 5, and 10 mol%) were synthesized by the foam replica and melting method. The thermodynamic evolution, phase composition, microstructure, ion release, in vitro bioactivity, and oxygen density of the scaffolds were characterized. The proliferation of murine long bone osteocyte Y4 cells was studied by cell culture. The survival rate of the BGs evaluated the antibacterial activity and Escherichia coli strains in co-culture. The results indicated that the process window decreases with the increase of dopants. All the samples have a pore structure size of 200–400 μm. When the scaffolds were immersed in simulated body fluid for 28 days, hydroxyapatite formation was not affected, but the degradation process was retarded. The glass network packing and ionic radii variations of the substitution ions control surface degradation, glass dissolution, and ion release. MTT results revealed that 5Sr-BG had a significant effect on promoting cell proliferation and none of the BGs were cytotoxicity. Sr-BGs and Zn-BGs exhibited significantly inhibited growth against E. coli bacterial strains. Generally, these results showed the 5Sr-BG scaffold with high vitro bioactivity, cell proliferation, and antibacterial property is an important candidate material for bone tissue regeneration and repair.